Select the simplified expression for 8(x - 8) - 6(x - 1) + 7x.

Question

Asked 5/4/2014 6:27:54 PM

Updated 5/4/2014 8:57:18 PM

1 Answer/Comment

Flagged by yeswey [5/4/2014 8:56:33 PM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

Question

Asked 5/4/2014 6:27:54 PM

Updated 5/4/2014 8:57:18 PM

1 Answer/Comment

Flagged by yeswey [5/4/2014 8:56:33 PM]

Rating

8

8(x - 8) - 6(x - 1) + 7x

= 8x - 64 - 6x + 6 + 7x

= 9x - 58

= 8x - 64 - 6x + 6 + 7x

= 9x - 58

Added 5/4/2014 8:57:18 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/4/2014 9:02:32 PM]

simplify the expression, -15y7 * 4yc7

Question

Not Answered

Updated 4/29/2014 9:08:42 PM

1 Answer/Comment

Calculate the product of 1/6 and 1/5 **Weegy:** The product of 1/6 and 1/5 is 1/30.
(More)

Question

Expert Answered

Updated 5/5/2014 3:18:38 PM

5 Answers/Comments

1/6 * 1/5;

(1*1)/(6 * 5)

= 1/30

(1*1)/(6 * 5)

= 1/30

Added 5/5/2014 2:52:21 PM

This answer has been confirmed as correct and helpful.

emdjay23, as stated on the rules, it's important to show the solutions for math questions and links are not required. Please make sure to provide a solution to make your answer more helpful to the user. Thanks.

Added 5/5/2014 2:53:18 PM

Determine the value of 5(x + 8) - 3 when x = 3.

Question

Updated 7/5/2018 5:24:39 AM

1 Answer/Comment

5(x + 8) - 3 when x = 3.

5(3 + 8) - 3

= 5(11) - 3

= 55 - 3

= 52

5(3 + 8) - 3

= 5(11) - 3

= 55 - 3

= 52

Added 7/5/2018 5:24:39 AM

This answer has been confirmed as correct and helpful.

What is the expression that represents the statement "5 times a number"?

Question

Not Answered

Updated 6/13/2014 3:21:52 PM

1 Answer/Comment

5n represents "5 times a number".

Added 6/13/2014 3:21:52 PM

This answer has been confirmed as correct and helpful.

Select the simplified expression for 8(x - 8) - 6(x - 1) + 7x.
9x + 70
9x - 9
9x - 70
9x - 58
**Weegy:** 7x + [x - (5 + x)] = 7x - 5 (More)

Question

Updated 11/12/2014 11:02:12 PM

1 Answer/Comment

8(x - 8) - 6(x - 1) + 7x

= 8x - 64 - 6x + 6 + 7x

= 2x + 7x - 58

= 9x - 58

= 8x - 64 - 6x + 6 + 7x

= 2x + 7x - 58

= 9x - 58

Added 11/12/2014 11:02:12 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [11/12/2014 11:04:09 PM], Rated good by andrewpallarca

38,917,144

questions answered

There are no comments.